KEPUASAN KERJA, MOTIVASI, KOMITMEN KARYAWAN & KUALITAS PELAYANAN DI LINGKUNGAN PDAM KABUPATEN CIANJUR - Permana, Arie Soleh (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2021)
This study applied the theoretical framework to examine how the mediating role of organizational commitment in the relationship between work motivation, job satisfaction and service quality in nonprofit sport organizations. A sample of 50 employee was randomly taken from 192 employee of PDAM Cianjur’s District. The path analysis was used to analyse the hypothesised relationships. The result revealed that job satisfaction and work motivation affects positively on organizational commitment. A significant mediation effect of organizational commitment was found on the relationship between work motivation and service quality